Socio–Cultural Exclusion and Inclusion of Trans-genders in India - Konduru, Delliswararao; Hangsing, Chongneikim (International Journal of Social Sciences and Management, 2018)
With an increasing issues in India, one of the major social issues concerning within the country is the identity of transgender. Over a decade in India, the issue of transgender has been a matter of quest in both social and cultural context where gender equality still remains a challenging factor towards the development of society because gender stratification much exists in every spheres of life as one of the barriers prevailing within the social structure of India. Similarly the issue of transgender is still in debate and uncertain even after the Supreme of India recognise them as a third gender people. In this paper I express my views on the issue of transgender in defining their socio – cultural exclusion and inclusion problems and development process in the society, and Perceptions by the main stream. Int. J. Soc. Sc. Manage. Vol. 5, Issue-1: 10-17